Silicon-titanium composite negative electrode material and preparation method thereof and lithium ion battery

Silica dioxide, titanium-containing blast furnace slag and magnesium powder were mixed by magnesium thermal reduction method to generate TiSi2, which solved the problem of insufficient dispersion and conductivity of silicon-titanium composite anode material, improved the performance of lithium-ion batteries, and simplified the process and reduced costs.

CN115312718BActive Publication Date: 2025-03-28EVE POWER CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210907344.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2025-03-28
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

The existing silicon-titanium composite anode materials and their preparation methods have problems such as poor dispersion, poor uniformity, poor conductivity, poor rate performance and poor cycle stability, and are complex in the process and high in the preparation cost.

Method used

By mixing silica, titanium-containing blast furnace slag and magnesium powder, thermal reduction of magnesium is performed to generate TiSi2, which is conducive to absorbing heat and preventing the melting and bonding of nano-silicon particles, and improving dispersion and conductivity.

Benefits of technology

The dispersion and conductivity of the silicon-titanium composite negative electrode material are improved, the rate performance and cycle stability of lithium-ion batteries are enhanced, and the process is simple and the preparation cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115312718B_ABST
    Figure CN115312718B_ABST
Patent Text Reader

Abstract

The present invention provides a silicon-titanium composite negative electrode material and a preparation method thereof and a lithium-ion battery. The preparation method comprises: mixing silicon dioxide, titanium-containing blast furnace slag and magnesium powder, and performing magnesium thermal reduction to obtain the silicon-titanium composite negative electrode material; the mass fraction of titanium dioxide in the titanium-containing blast furnace slag is 10-23wt%; the mass ratio of silicon dioxide, titanium-containing blast furnace slag and magnesium powder is (8-12):(6-12):(6-10). The preparation method of the present invention utilizes the titanium-containing blast furnace slag as a resource; the TiSi2 generated during the magnesium thermal reduction process is conducive to absorbing a large amount of heat generated during the reaction process, preventing the melting and bonding of nano-silicon particles, and improving the dispersibility of the silicon-titanium composite negative electrode material; the lithium-ion battery prepared with the silicon-titanium composite negative electrode material has good rate performance; the lithium-ion battery prepared with the silicon-titanium composite negative electrode material has good cycle stability; the preparation method is simple in process and low in preparation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of silicon-carbon composite materials, and relates to a silicon-titanium composite negative electrode material, and in particular to a silicon-titanium composite negative electrode material, a preparation method thereof, and a lithium ion battery. Background Art

[0002] Nanostructured silicon has broad application prospects in new energy materials, solar energy, microelectronics, biochemistry and environmental protection. Traditional carbon thermal reduction can obtain metallurgical silicon with high purity. However, since the reaction temperature of traditional carbon thermal reduction is often above 1400 degrees, it is difficult to obtain widely applicable nano-scale silicon materials. At present, the methods for preparing nano-silicon materials mainly include chemical or electrochemical etching, rapid cooling, laser ablation, silicon tetrachloride reduction method and silane thermal decomposition method. These preparation methods generally have the disadvantages of high cost, complex equipment structure, high toxicity and low yield, which are not conducive to large-scale production of nano-silicon. Metal thermal reduction of silicon is considered to have the potential to overcome the above problems, but traditional metal thermal reduction of silicon also has some problems. For example, for magnesium thermal or aluminum thermal reduction, although porous silicon with nanostructure can be obtained after reduction, its nanostructure is due to the disordered stacking of silicon atoms in the reduction process and the melt adhesion of the nanostructure, resulting in poor homogenization and dispersion of the nanostructure, thereby affecting their performance in specific applications.

[0003] CN111834610A discloses a method for preparing a lithium-ion battery silicon-carbon composite negative electrode material based on magnesium thermal reduction. The method first uses graphite and carboxymethyl cellulose (CMC) or hydroxypropyl cellulose (HPC) solution to prepare a high-concentration graphite dispersion, then adds nano-silicon dioxide sol to the graphite dispersion to make it evenly dispersed, then spray-dries the dispersion to form a graphite / silicon dioxide composite, then performs a magnesium thermal reduction reaction, and finally adds styrene-acrylonitrile copolymer emulsion and performs high-temperature treatment to obtain a lithium-ion battery silicon-carbon composite material.

[0004] CN106374088A discloses a method for preparing a silicon-carbon composite material by magnesium thermal reduction, which belongs to the technical field of composite material preparation. The method comprises: (1) mixing a silicon dioxide source, an organic carbon source and a solvent, ball milling to obtain a homogenous mixture, and drying to obtain a silicon dioxide-carbon precursor composite material; (2) mixing the silicon dioxide-carbon precursor composite material with magnesium powder to perform magnesium thermal reduction reaction, collecting the product and acid-washing and water-washing, and drying to obtain the silicon-carbon composite material.

[0005] CN105762338A discloses a method for preparing a silicon-carbon negative electrode material for a lithium-ion battery by utilizing magnesium thermal reduction, comprising: preparing a mixed solution of sodium silicate, glucose and sodium chloride; heating and drying to obtain a brown caramel-like precursor; heating to 650°C and calcining in an Ar atmosphere to obtain a sodium silicate / carbon precursor; utilizing the principle of strong acid to produce weak acid, adding HCl to the sodium silicate / carbon precursor to prepare a mixed solution, subsequently placing the mixed solution in a 170°C oven for drying, and washing the sample with water to obtain a silicon dioxide / porous carbon composite material; uniformly mixing the silicon dioxide / porous carbon composite material with magnesium powder and sodium chloride, calcining at 700°C, and obtaining a silicon-carbon composite material after acid treatment, water washing and drying.

[0006] The currently disclosed silicon-titanium composite negative electrode materials and their preparation methods have certain defects, such as poor dispersibility, poor uniformity, poor conductivity, poor rate performance and poor cycle stability of the silicon-titanium composite negative electrode materials, and the preparation method of the silicon-titanium composite negative electrode materials has complex process and high preparation cost. Therefore, it is very important to develop and design a new type of silicon-titanium composite negative electrode material and its preparation method. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention aims to provide a silicon-titanium composite negative electrode material and a preparation method thereof and a lithium-ion battery. The preparation method of the present invention makes use of titanium-containing blast furnace slag as a resource; the TiSi generated in the magnesium thermal reduction process 2 It is beneficial to absorb a large amount of heat generated during the reaction, prevent the melting and bonding of nano-silicon particles, and improve the dispersibility of the silicon-titanium composite negative electrode material; the lithium-ion battery prepared with the silicon-titanium composite negative electrode material has good rate performance; the lithium-ion battery prepared with the silicon-titanium composite negative electrode material has good cycle stability; the preparation method is simple in process and low in preparation cost.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a silicon-titanium composite negative electrode material, the preparation method comprising:

[0010] Mixing silicon dioxide, titanium-containing blast furnace slag and magnesium powder, and performing magnesium thermal reduction to obtain a silicon-titanium composite negative electrode material;

[0011] The mass fraction of titanium dioxide in the titanium-containing blast furnace slag is 10 to 23 wt%;

[0012] The mass ratio of silicon dioxide, titanium-containing blast furnace slag and magnesium powder is (8-12):(6-12):(6-10).

[0013] The titanium-containing blast furnace slag of the present invention is a high-yield hazardous waste material that is difficult to treat and is usually disposed of by landfill, which causes great pollution to the environment. The main component of the titanium-containing blast furnace slag is TiO 2 ,Fe,SiO 2 、MgO、Al 2 O 3 、CaO、MnO、V 2 O 5 , Ga 2 O 3 Cr 2 O 3 wait.

[0014] The present invention limits the mass ratio of silicon dioxide to titanium-containing blast furnace slag to (8-12):(6-12), for example, it can be 8:6, 8:8, 8:9, 8:11, 8:12, 9:6, 9:8, 9:11, 9:12, 10:6, 10:7, 10:9, 10:11, 10:12, 11:6, 11:7, 11:9, 11:10, 11:12, 12:6, 12:7 or 12:11, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0015] The present invention limits the mass ratio of silicon dioxide to magnesium powder to (8-12):(6-10), for example, it can be 8:6, 8:7, 8:8, 8:9, 8:10, 9:6, 9:7, 9:10, 10:6, 10:7, 10:9, 11:6, 11:7, 11:9, 11:10, 12:6, 12:7, 12:9 or 12:10, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0016] The preparation method of the present invention introduces the cheap titanium-containing blast furnace slag produced in the steel smelting process into the magnesium thermal reduction process of silicon dioxide, thereby utilizing the titanium-containing blast furnace slag as a resource, solving the problem of treating the titanium-containing blast furnace slag waste, and turning waste into treasure; in the magnesium thermal reduction process, the titanium dioxide reduction product titanium reacts with silicon to generate TiSi 2 , TiSi 2 The generation of TiSi is beneficial to absorb the large amount of heat generated during the reaction, prevent the melting and bonding of nano-silicon particles, and improve the dispersibility of silicon-titanium composite negative electrode materials; 2 It also has good electrical conductivity, thereby improving the electronic conductivity of silicon-titanium composite negative electrode materials. Lithium-ion batteries prepared with silicon-titanium composite negative electrode materials have good rate performance; TiSi 2 The invention can act as an anchor point to buffer the volume change of silicon material during the electrochemical cycle, and the lithium ion battery prepared with the silicon-titanium composite negative electrode material has good cycle stability; the preparation method is simple in process and low in preparation cost.

[0017] Preferably, the mixing further includes mixing of a reducing aid.

[0018] Preferably, the reducing aid comprises any one of sodium chloride, sodium bromide, sodium fluoride, sodium iodide, potassium chloride, potassium bromide, potassium fluoride, and potassium iodide, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of sodium chloride and sodium bromide, a combination of sodium bromide and sodium fluoride, a combination of sodium iodide and potassium chloride, a combination of potassium bromide and potassium fluoride, a combination of sodium chloride and potassium iodide, a combination of sodium chloride, sodium bromide and sodium fluoride, or a combination of sodium chloride, sodium bromide, sodium fluoride and potassium chloride.

[0019] Preferably, the mass ratio of the reducing agent to silicon dioxide is 100:(8-12), for example, it can be 100:8, 100:8.5, 100:9, 100:9.5, 100:10, 100:10.5, 100:11 or 100:12, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the magnesium thermal reduction is carried out in a reducing atmosphere.

[0021] Preferably, the reducing atmosphere is a mixture of reducing gas and protective gas.

[0022] Preferably, the reducing gas comprises any one of hydrogen, carbon monoxide, hydrogen sulfide, methane, sulfur monoxide or a combination of at least two thereof. Typical but non-limiting combinations include a combination of hydrogen and carbon monoxide, a combination of carbon monoxide and hydrogen sulfide, a combination of methane and sulfur monoxide, a combination of hydrogen, carbon monoxide and hydrogen sulfide, or a combination of hydrogen, carbon monoxide, hydrogen sulfide and methane.

[0023] Preferably, the protective gas comprises an inert gas and / or nitrogen.

[0024] The inert gas described in the present invention includes any one of helium, neon, argon, krypton and xenon, or a combination of at least two of them.

[0025] Preferably, the volume fraction of the reducing gas in the reducing atmosphere is 3% to 10% based on the volume of the reducing atmosphere, and the remainder is protective gas.

[0026] The present invention limits the volume fraction of reducing gas in the reducing atmosphere to 3% to 10%, for example, it can be 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the magnesium thermal reduction comprises sequential heating and heat preservation.

[0028] Preferably, the heating rate is 3-15°C / min, and the terminal temperature of the heating is 600-900°C.

[0029] The present invention limits the heating rate to 3 to 15°C / min, for example, it can be 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min or 15°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0030] The present invention limits the terminal temperature of the heating to 600-900°C, for example, it can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the insulation time is 4 to 10 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the preparation method further comprises pickling after magnesium thermal reduction.

[0033] In the present invention, hydrochloric acid and / or sulfuric acid are used for pickling.

[0034] Preferably, the preparation of silicon dioxide comprises the following steps:

[0035] (1) mixing water, ethanol and aqueous ammonia to obtain a first mixed solution;

[0036] (2) mixing ethanol and ethyl silicate to obtain a second mixed solution;

[0037] (3) mixing the first mixed liquid and the second mixed liquid, and obtaining silicon dioxide after solid-liquid separation;

[0038] There is no particular order in which steps (1) and (2) are performed.

[0039] Preferably, the mass ratio of water, ethanol and aqueous ammonia in step (1) is (40-60):(28-36):(15-20).

[0040] The present invention defines the mass ratio of water to ethanol in step (1) as (40-60):(28-36), for example, 40:28, 40:29, 40:31, 40:33, 40:36, 43:28, 43:29, 43:31, 43:33, 43:36, 47:28, 47:29, 47:31, 47:33, 47:36, 49:28, 49: 29, 49:31, 49:33, 49:36, 53:28, 53:29, 53:31, 53:33, 53:36, 57:28, 57:29, 57:31, 57:33, 57:36, 60:28, 60:29, 60:31, 60:33 or 60:36, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] The present invention limits the mass ratio of ethanol to aqueous ammonia in step (1) to (28-36):(15-20), for example, it can be 28:15, 28:17, 28:19, 28:20, 29:15, 29:17, 29:19, 29:20, 31:15, 31:17, 31:19, 31:20, 33:15, 33:17, 33:19, 33:20, 36:15, 36:17, 36:19 or 36:20, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0042] Preferably, the mass ratio of ethanol to ethyl silicate in step (2) is (80-100):(6-12), for example, 80:6, 80:7, 80:9, 80:11, 80:12, 87:6, 87:7, 87:9, 87:11, 87:12, 89:6, 89:7, 89:9, 89:11, 89:12, 91:6, 91:7, 91:9, 91:11, 91:12, 93:6, 93:7, 93:9, 93:11, 93:12, 97:6, 97:7, 97:9, 97:11, 97:12, 100:6, 100:7, 100:9, 100:11 or 100:12, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] Preferably, in step (3), the mass ratio of the first mixed liquid to the second mixed liquid is (0.9-1.2):1, for example, it can be 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1, 1.15:1 or 1.2:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] Preferably, the mixing method in step (1) includes stirring, and the stirring speed is 400-700 r / min and the time is 1-6 min.

[0045] The present invention limits the stirring speed to 400-700 r / min, for example, it can be 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, 650 r / min or 700 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] The present invention limits the stirring time to 1 to 6 minutes, for example, it can be 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes or 6 minutes, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Preferably, the mixing method in step (2) includes stirring, and the stirring speed is 400-700 r / min and the time is 1-6 min.

[0048] The present invention limits the stirring speed to 400-700 r / min, for example, it can be 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, 650 r / min or 700 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] The present invention limits the stirring time to 1 to 6 minutes, for example, it can be 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes or 6 minutes, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the mixing method in step (3) includes stirring, and the stirring speed is 400-700 r / min and the time is 1-6 h.

[0051] The present invention limits the stirring speed to 400-700 r / min, for example, it can be 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, 650 r / min or 700 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] The present invention limits the stirring time to 1 to 6 hours, for example, it can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] Preferably, the preparation of silicon dioxide further comprises washing and drying in sequence after solid-liquid separation.

[0054] Preferably, the drying temperature is 60-80° C. and the drying time is 10-14 hours.

[0055] The present invention limits the drying temperature to 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] The present invention limits the drying time to 10 to 14 hours, for example, it can be 10 hours, 11 hours, 12 hours, 13 hours or 14 hours, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] As a preferred technical solution of the preparation method described in the first aspect, the preparation method comprises:

[0058] A reducing agent, silicon dioxide, titanium dioxide mass fraction of 10 to 23 wt% and magnesium powder are mixed in a mass ratio of 100:(8 to 12):(6 to 12):(6 to 10); in a reducing atmosphere formed by a mixture of reducing gas and protective gas, the temperature is raised to 600 to 900° C. at a rate of 3 to 15° C. / min and kept warm for 4 to 10 hours; based on the volume of the reducing atmosphere, the volume fraction of the reducing gas in the reducing atmosphere is 3% to 10%, and the remainder is protective gas; after pickling, a silicon-titanium composite negative electrode material is obtained.

[0059] In a second aspect, the present invention provides a silicon-titanium composite negative electrode material, wherein the silicon-titanium composite negative electrode material is obtained by the preparation method described in the first aspect.

[0060] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode plate, a separator and a negative electrode plate stacked in sequence, wherein the negative electrode plate comprises a current collector and a negative electrode active layer coated on the surface of the current collector, and the negative electrode active layer comprises the silicon-titanium composite negative electrode material described in the second aspect.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] (1) The preparation method of the present invention introduces cheap titanium-containing blast furnace slag produced in the steel smelting process into the magnesium thermal reduction process of silicon dioxide, thereby utilizing the titanium-containing blast furnace slag as a resource, solving the problem of handling titanium-containing blast furnace slag waste, and turning waste into treasure;

[0063] (2) In the magnesium thermal reduction process of the present invention, the titanium oxide reduction product titanium reacts with silicon to generate TiSi 2 , TiSi2 The generation of is beneficial to absorb the large amount of heat generated during the reaction, prevent the melting and bonding of nano-silicon particles, and improve the dispersibility of silicon-titanium composite negative electrode materials;

[0064] (3) TiSi generated by the magnesium thermal reduction process of the present invention 2 It has good electrical conductivity, thus improving the electronic conductivity of silicon-titanium composite negative electrode materials. Lithium-ion batteries prepared with silicon-titanium composite negative electrode materials have good rate performance.

[0065] (4) TiSi generated by the magnesium thermal reduction process of the present invention 2 It can act as an anchor point to buffer the volume change of silicon materials during the electrochemical cycle, and lithium-ion batteries prepared with silicon-titanium composite negative electrode materials have good cycle stability;

[0066] (5) The preparation method of the present invention has simple process and low preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 This is a SEM image of the silicon-titanium composite negative electrode material in Example 1.

[0068] Figure 2 This is a graph showing the rate performance test results of a lithium-ion battery prepared using the silicon-titanium composite negative electrode material in Example 1.

[0069] Figure 3 This is a test result diagram of the cycle stability test of the lithium-ion battery prepared with the silicon-titanium composite negative electrode material in Example 1. DETAILED DESCRIPTION

[0070] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0071] Example 1

[0072] This embodiment provides a method for preparing a silicon-titanium composite negative electrode material, the preparation method comprising:

[0073] Sodium chloride, silicon dioxide, titanium dioxide with a mass fraction of 16wt% titanium-containing blast furnace slag and magnesium powder are mixed in a mass ratio of 100:10:9:7; in a reducing atmosphere formed by a mixture of hydrogen and argon, the temperature is raised to 700°C at a rate of 6°C / min and kept warm for 8 hours; based on the volume of the reducing atmosphere, the volume fraction of hydrogen in the reducing atmosphere is 6%, and the balance is argon; after hydrochloric acid pickling, a silicon-titanium composite negative electrode material is obtained.

[0074] The preparation of the silicon dioxide comprises the following steps:

[0075] (1) mixing water, ethanol and ammonia water in a mass ratio of 50:32:17 at a speed of 550 r / min and stirring for 4 min to obtain a first mixed solution;

[0076] (2) mixing ethanol and ethyl silicate in a mass ratio of 90:8 at a speed of 550 r / min and stirring for 3 min to obtain a second mixed solution;

[0077] (3) mixing the first mixed liquid and the second mixed liquid in a mass ratio of 1:1 at a speed of 550 r / min for 3 h, separating the solid and the liquid, washing with water, and drying at 75° C. for 11 h to obtain silicon dioxide;

[0078] There is no particular order in which steps (1) and (2) are performed.

[0079] Example 2

[0080] This embodiment provides a method for preparing a silicon-titanium composite negative electrode material, the preparation method comprising:

[0081] Sodium chloride, silicon dioxide, titanium dioxide, titanium blast furnace slag with a mass fraction of 13wt% and magnesium powder are mixed in a mass ratio of 100:8:6:10; in a reducing atmosphere formed by a mixture of hydrogen and nitrogen, the temperature is raised to 700°C at a rate of 9°C / min and kept warm for 6 hours; based on the volume of the reducing atmosphere, the volume fraction of hydrogen in the reducing atmosphere is 4.5%, and the balance is nitrogen; after hydrochloric acid pickling, a silicon-titanium composite negative electrode material is obtained.

[0082] The preparation of the silicon dioxide comprises the following steps:

[0083] (1) mixing water, ethanol and ammonia water in a mass ratio of 40:36:15 at a speed of 600 r / min for 3 min to obtain a first mixed solution;

[0084] (2) mixing ethanol and ethyl silicate in a mass ratio of 100:12 with stirring at a speed of 600 r / min for 4 min to obtain a second mixed solution;

[0085] (3) stirring the first mixed liquid and the second mixed liquid at a mass ratio of 0.95:1 at a speed of 500 r / min for 5 hours, separating the solid and the liquid, washing with water, and drying at 70° C. for 12 hours to obtain silicon dioxide;

[0086] There is no particular order in which steps (1) and (2) are performed.

[0087] Example 3

[0088] This embodiment provides a method for preparing a silicon-titanium composite negative electrode material, the preparation method comprising:

[0089] Sodium bromide, silicon dioxide, titanium dioxide with a mass fraction of 20wt% titanium-containing blast furnace slag and magnesium powder are mixed in a mass ratio of 100:12:12:6; in a reducing atmosphere formed by a mixture of carbon monoxide and nitrogen, the temperature is raised to 800°C at a rate of 12°C / min and kept warm for 4 hours; based on the volume of the reducing atmosphere, the volume fraction of carbon monoxide in the reducing atmosphere is 8%, and the balance is nitrogen; after pickling with sulfuric acid, a silicon-titanium composite negative electrode material is obtained.

[0090] The preparation of the silicon dioxide titanium comprises the following steps:

[0091] (1) mixing water, ethanol and ammonia water in a mass ratio of 60:36:20 at a speed of 500 r / min and stirring for 5 min to obtain a first mixed solution;

[0092] (2) mixing ethanol and ethyl silicate in a mass ratio of 80:6 at a speed of 500 r / min and stirring for 5 min to obtain a second mixed solution;

[0093] (3) mixing the first mixed liquid and the second mixed liquid in a mass ratio of 1.1:1 at a speed of 600 r / min for 4 h, separating the solid and the liquid, washing with water, and drying at 65° C. for 13 h to obtain silicon dioxide;

[0094] There is no particular order in which steps (1) and (2) are performed.

[0095] Example 4

[0096] This embodiment provides a method for preparing a silicon-titanium composite negative electrode material, the preparation method comprising:

[0097] Potassium chloride, silicon dioxide, titanium dioxide with a mass fraction of 23wt% titanium-containing blast furnace slag and magnesium powder are mixed in a mass ratio of 100:12:6:6; in a reducing atmosphere formed by a mixture of hydrogen sulfide and helium, the temperature is raised to 600°C at a rate of 3°C / min and kept warm for 10 hours; based on the volume of the reducing atmosphere, the volume fraction of hydrogen sulfide in the reducing atmosphere is 10%, and the remainder is helium; after pickling with sulfuric acid, a silicon-titanium composite negative electrode material is obtained.

[0098] The preparation of the silicon dioxide comprises the following steps:

[0099] (1) mixing water, ethanol and ammonia water in a mass ratio of 60:28:15 at a speed of 400 r / min and stirring for 6 min to obtain a first mixed solution;

[0100] (2) mixing ethanol and ethyl silicate in a mass ratio of 80:12 at a speed of 400 r / min and stirring for 6 min to obtain a second mixed solution;

[0101] (3) stirring the first mixed liquid and the second mixed liquid at a mass ratio of 0.9:1 at a speed of 400 r / min for 6 hours, separating the solid and the liquid, washing with water, and drying at 60° C. for 14 hours to obtain silicon dioxide;

[0102] There is no particular order in which steps (1) and (2) are performed.

[0103] Example 5

[0104] This embodiment provides a method for preparing a silicon-titanium composite negative electrode material, the preparation method comprising:

[0105] Potassium bromide, silicon dioxide, titanium dioxide, titanium blast furnace slag with a mass fraction of 10wt% and magnesium powder are mixed in a mass ratio of 100:8:12:10; in a reducing atmosphere formed by a mixture of hydrogen and neon, the temperature is raised to 900°C at a rate of 15°C / min and kept warm for 4 hours; based on the volume of the reducing atmosphere, the volume fraction of hydrogen in the reducing atmosphere is 3%, and the balance is neon; after hydrochloric acid pickling, a silicon-titanium composite negative electrode material is obtained.

[0106] The preparation of the silicon dioxide comprises the following steps:

[0107] (1) mixing water, ethanol and ammonia water in a mass ratio of 40:28:20 at a speed of 700 r / min and stirring for 1 min to obtain a first mixed solution;

[0108] (2) mixing ethanol and ethyl silicate in a mass ratio of 100:6 with stirring at a speed of 700 r / min for 1 min to obtain a second mixed solution;

[0109] (3) stirring the first mixed liquid and the second mixed liquid at a mass ratio of 1.2:1 at a rotation speed of 700 r / min for 1 h, separating the solid and the liquid, washing with water, and drying at 80° C. for 10 h to obtain silicon dioxide.

[0110] Example 6

[0111] This embodiment provides a method for preparing a silicon-titanium composite negative electrode material, which is the same as that of Embodiment 1 except that the mass ratio of silicon dioxide to titanium-containing blast furnace slag is 5:12.

[0112] Example 7

[0113] This embodiment provides a method for preparing a silicon-titanium composite negative electrode material, which is the same as that of Embodiment 1 except that the mass ratio of silicon dioxide to titanium-containing blast furnace slag is 12:4.

[0114] Example 8

[0115] This embodiment provides a method for preparing a silicon-titanium composite negative electrode material, which is the same as that of Embodiment 1 except that the mass ratio of sodium chloride to silicon dioxide is 100:15.

[0116] Example 9

[0117] This embodiment provides a method for preparing a silicon-titanium composite negative electrode material, which is the same as that of Embodiment 1 except that the mass ratio of sodium chloride to silicon dioxide is 100:5.

[0118] Comparative Example 1

[0119] This comparative example provides a method for preparing a silicon negative electrode material, which is the same as Example 1 except that the titanium-containing blast furnace slag is omitted.

[0120] The silicon-titanium composite negative electrode material in Example 1 was tested by field emission scanning electron microscopy, and the obtained SEM image is as follows: Figure 1 As shown;

[0121] The conductivity of the silicon-titanium composite negative electrode materials in Examples 1 to 9 and the silicon negative electrode material in Comparative Example 1 was tested, and the conductivity obtained is shown in Table 1;

[0122] A lithium ion battery is prepared using the silicon-titanium composite negative electrode materials in Examples 1 to 9 and the silicon negative electrode material in Comparative Example 1, and the preparation method is as follows:

[0123] The silicon-titanium composite negative electrode material or silicon negative electrode material is weighed with acetylene black and sodium alginate in a mass ratio of 60:20:20, mixed evenly, added with NMP and stirred for 1 hour to form a viscous slurry, evenly coated on aluminum foil, and then baked in a vacuum oven at 80°C, pressed into sheets, and cut into positive electrode sheets with a diameter of 13 mm. A pure lithium sheet with a diameter of 16 mm is used as a negative electrode sheet, a mixed solution of 1 mol / L LiPF6 + DEC / EC (volume ratio 1:1) + 10% FEC is used as an electrolyte, and a polypropylene microporous membrane is used as a diaphragm, and assembled into a lithium-ion battery in a glove box filled with argon;

[0124] The lithium ion battery is subjected to a rate performance test, and the test method is: in the voltage range of 3.0 to 0.01 V, the lithium ion battery is charged and discharged at different rates, and the average discharge capacity C1 of the prepared lithium ion battery at a current density of 0.21 A / g and the average discharge capacity C2 at a current density of 8.4 A / g are shown in Table 1;

[0125] The rate performance test results of the lithium ion battery prepared with the silicon-titanium composite negative electrode material in Example 1 are as follows: Figure 2 As shown;

[0126] The lithium ion battery was subjected to a cycle stability test, and the test method was as follows: in a voltage range of 3.0 to 0.01 V, the lithium ion battery was charged and discharged at a current density of 0.84 A / g, and after 200 cycles, the specific capacity and coulombic efficiency of the lithium ion battery were obtained as shown in Table 1;

[0127] The test results of the cycle stability test of the lithium ion battery prepared with the silicon-titanium composite negative electrode material in Example 1 are as follows: Figure 3 shown.

[0128] Table 1

[0129]

[0130]

[0131] From Table 1 and Figures 1 to 3 We can get:

[0132] (1) The silicon-titanium composite negative electrode material obtained in Examples 1 to 5 has good dispersibility and high electrical conductivity, and the lithium ion battery prepared with the silicon-titanium composite negative electrode material has excellent rate performance and high cycle stability; the preparation method of the present invention introduces the cheap titanium-containing blast furnace slag produced in the steel smelting process into the magnesium thermal reduction process of silicon dioxide, thereby utilizing the titanium-containing blast furnace slag as a resource, solving the problem of treating titanium-containing blast furnace slag waste, and turning waste into treasure; in the magnesium thermal reduction process, the titanium reduction product of titanium dioxide reacts with silicon to generate TiSi 2 , TiSi 2 The generation of TiSi is beneficial to absorb the large amount of heat generated during the reaction, prevent the melting and bonding of nano-silicon particles, and improve the dispersibility of silicon-titanium composite negative electrode materials; 2 It also has good electrical conductivity, thereby improving the electronic conductivity of silicon-titanium composite negative electrode materials. Lithium-ion batteries prepared with silicon-titanium composite negative electrode materials have good rate performance; TiSi 2 It can act as an anchor point to buffer the volume change of silicon materials during the electrochemical cycle, and the lithium-ion battery prepared with the silicon-titanium composite negative electrode material has good cycle stability; the preparation method is simple in process and low in preparation cost;

[0133] (2) By comparing Example 1 with Examples 6 and 7, it can be seen that the mass ratio of silicon dioxide to titanium-containing blast furnace slag will affect the performance of silicon-titanium composite negative electrode materials and lithium-ion batteries; when the mass ratio of silicon dioxide to titanium-containing blast furnace slag is low, the conductivity will increase, the average discharge capacity will decrease at a current density of 0.21A / g, the average discharge capacity will decrease at a current density of 8.4A / g, the specific capacity will decrease after 200 cycles, and the coulomb efficiency will decrease after 200 cycles. This is due to the TiSi generated by the magnesium thermal process. 2 Too much, the overall capacity of the material is reduced, and TiSi 2Excessive addition leads to agglomeration of materials, resulting in poor cycle reversibility; when the mass ratio of silicon dioxide to titanium-containing blast furnace slag is too high, it will lead to a decrease in conductivity, a decrease in the average discharge capacity at a current density of 0.21A / g, a decrease in the average discharge capacity at a current density of 8.4A / g, a decrease in the specific capacity after 200 cycles, and a decrease in the coulombic efficiency after 200 cycles. This is due to the TiSi in the material. 2 As the content of is reduced, the effect of improving the overall conductivity of the material is reduced, resulting in poor electrochemical performance.

[0134] (3) By comparing Example 1 with Examples 8 and 9, it can be seen that the mass ratio of the reduction aid to silicon dioxide will affect the performance of the silicon-titanium composite negative electrode material and the lithium-ion battery; when the mass ratio of the reduction aid to silicon dioxide is low, it will lead to a decrease in conductivity, a decrease in the average discharge capacity at a current density of 0.21A / g, a decrease in the average discharge capacity at a current density of 8.4A / g, a decrease in the specific capacity after 200 cycles, and a decrease in the coulombic efficiency after 200 cycles. This is because the amount of the reduction aid is low, resulting in the decrease of SiO 2 Insufficient reduction and TiSi 2 The formation of is also reduced, and the overall conductivity of the material is also reduced; when the mass ratio of the reducing agent to silicon dioxide is too high, the conductivity will decrease, the average discharge capacity will decrease at a current density of 0.21A / g, the average discharge capacity will decrease at a current density of 8.4A / g, the specific capacity will decrease after 200 cycles, and the coulomb efficiency will decrease after 200 cycles. This is because the excessive amount of reducing agent leads to excessive heat release during the magnesium heating process, which makes the material agglomerate seriously, resulting in poor performance of the material;

[0135] (4) By comparing Example 1 with Comparative Example 1, it can be seen that the addition of titanium-containing blast furnace slag is beneficial to improving the performance of silicon-titanium composite negative electrode materials and lithium-ion batteries; after the addition of titanium-containing blast furnace slag, the conductivity of the obtained silicon-titanium composite negative electrode material increases, the average discharge capacity at a current density of 0.21A / g increases, the average discharge capacity at a current density of 8.4A / g increases, the specific capacity after 200 cycles increases, and the coulomb efficiency after 200 cycles increases. This is because after the addition of titanium-containing blast furnace slag, the TiSi generated in the magnesium thermal reduction process 2 It has good electrical conductivity, which improves the electrical conductivity of silicon-titanium composite negative electrode materials, making lithium-ion batteries prepared from silicon-titanium composite negative electrode materials have good rate performance; TiSi 2 During the electrochemical cycle, it can act as an anchor point to buffer the volume change of silicon materials. Lithium-ion batteries prepared with silicon-titanium composite negative electrode materials have good cycle stability.

[0136] In summary, the preparation method of the present invention introduces the cheap titanium-containing blast furnace slag produced in the steel smelting process into the magnesium thermal reduction process of silicon dioxide, and utilizes the titanium-containing blast furnace slag as a resource, solves the problem of treating titanium-containing blast furnace slag waste, and turns waste into treasure; in the magnesium thermal reduction process of the present invention, the reduction product of titanium dioxide reacts with silicon to generate TiSi 2 , TiSi 2 The generation of TiSi is beneficial to absorb the large amount of heat generated in the reaction process, prevent the melting and bonding of nano-silicon particles, and improve the dispersibility of the silicon-titanium composite negative electrode material; the TiSi generated by the magnesium thermal reduction process of the present invention 2 The TiSiO2 has good electrical conductivity, thereby improving the electronic conductivity of the silicon-titanium composite negative electrode material, and the lithium-ion battery prepared with the silicon-titanium composite negative electrode material has good rate performance; the TiSiO2 generated by the magnesium thermal reduction process of the present invention 2 During the electrochemical cycle, it can act as an anchor point to buffer the volume change of the silicon material. The lithium-ion battery prepared with the silicon-titanium composite negative electrode material has good cycle stability. The preparation method of the present invention has a simple process and low preparation cost.

[0137] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a silicon-titanium composite negative electrode material, characterized in that: The preparation method comprises: Mixing silicon dioxide, titanium-containing blast furnace slag, a reducing aid and magnesium powder, and performing magnesium thermal reduction to obtain a silicon-titanium composite negative electrode material; The main components of the titanium-containing blast furnace slag are TiO2, Fe, SiO2, MgO, Al2O3, CaO, MnO, V2O5, Ga2O3, and Cr2O3; The mass fraction of titanium dioxide in the titanium-containing blast furnace slag is 13 to 23 wt%; The mass ratio of silicon dioxide, titanium-containing blast furnace slag and magnesium powder is (8-12):(6-12):(6-10); The mass ratio of the reducing agent to silicon dioxide is 100:(8-12); During the magnesium thermal reduction process, titanium, a reduction product of titanium dioxide, reacts with silicon to generate TiSi2.

2. The preparation method according to claim 1, characterized in that: The reducing aid includes any one of sodium chloride, sodium bromide, sodium fluoride, sodium iodide, potassium chloride, potassium bromide, potassium fluoride or potassium iodide, or a combination of at least two thereof.

3. The preparation method according to claim 1, characterized in that: The magnesium thermal reduction is carried out in a reducing atmosphere.

4. The preparation method according to claim 3, characterized in that: The reducing atmosphere is formed by mixing reducing gas and protective gas.

5. The preparation method according to claim 4, characterized in that: The reducing gas includes any one of hydrogen, carbon monoxide, hydrogen sulfide, methane, and sulfur monoxide, or a combination of at least two of them.

6. The preparation method according to claim 4, characterized in that: The protective gas includes an inert gas and / or nitrogen.

7. The preparation method according to claim 4, characterized in that: Calculated as a percentage of the volume of the reducing atmosphere, the volume fraction of the reducing gas in the reducing atmosphere is 3% to 10%, and the remainder is protective gas.

8. The preparation method according to claim 1, characterized in that: The magnesium thermal reduction includes heating and heat preservation in sequence.

9. The preparation method according to claim 8, characterized in that: The heating rate is 3-15°C / min, and the terminal temperature of the heating is 600-900°C.

10. The preparation method according to claim 8, characterized in that: The insulation time is 4 to 10 hours.

11. The preparation method according to claim 1, characterized in that: The preparation method further comprises pickling after magnesium thermal reduction.

12. The preparation method according to claim 1, characterized in that: The preparation of the silicon dioxide comprises the following steps: (1) mixing water, ethanol and aqueous ammonia to obtain a first mixed solution; (2) mixing ethanol and ethyl silicate to obtain a second mixed solution; (3) mixing the first mixed liquid and the second mixed liquid, and obtaining silicon dioxide after solid-liquid separation; There is no particular order in which steps (1) and (2) are performed.

13. The preparation method according to claim 12, characterized in that: The mass ratio of water, ethanol and aqueous ammonia in step (1) is (40-60):(28-36):(15-20).

14. The preparation method according to claim 12, characterized in that: The mass ratio of ethanol to ethyl silicate in step (2) is (80-100):(6-12).

15. The preparation method according to claim 12, characterized in that: In step (3), the mass ratio of the first mixed liquid to the second mixed liquid is (0.9-1.2):

1.

16. The preparation method according to claim 12, characterized in that: The mixing method in step (1) includes stirring, and the stirring speed is 400-700 r / min and the time is 1-6 min.

17. The preparation method according to claim 12, characterized in that: The mixing method in step (2) includes stirring, and the stirring speed is 400-700 r / min and the time is 1-6 min.

18. The preparation method according to claim 12, characterized in that: The mixing method in step (3) includes stirring, and the stirring speed is 400-700 r / min and the time is 1-6 hours.

19. The preparation method according to claim 12, characterized in that: The preparation of silicon dioxide also includes washing and drying in sequence after solid-liquid separation.

20. The preparation method according to claim 19, characterized in that: The drying temperature is 60-80° C. and the drying time is 10-14 hours.

21. The preparation method according to claim 1, characterized in that: The preparation method comprises: A reducing aid, silicon dioxide, titanium-containing blast furnace slag whose main components are TiO2, Fe, SiO2, MgO, Al2O3, CaO, MnO, V2O5, Ga2O3, Cr2O3, and a magnesium powder whose mass fraction of titanium dioxide is 13-23wt% and a mixing mass ratio of 100:(8-12):(6-12):(6-10); in a reducing atmosphere formed by a mixture of reducing gas and protective gas, heating to 600-900°C at a rate of 3-15°C / min and keeping the temperature for 4-10h; in terms of the volume of the reducing atmosphere, the volume fraction of the reducing gas in the reducing atmosphere is 3%-10%, and the remainder is protective gas; after pickling, a silicon-titanium composite negative electrode material is obtained.

22. A silicon-titanium composite negative electrode material, characterized in that: The silicon-titanium composite negative electrode material is obtained by the preparation method according to any one of claims 1 to 21.

23. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a separator and a negative electrode sheet stacked in sequence, the negative electrode sheet comprises a current collector and a negative electrode active layer coated on the surface of the current collector, and the negative electrode active layer comprises the silicon-titanium composite negative electrode material according to claim 22.

Citation Information

Patent Citations

  • Method for preparing lithium battery silicon carbon anode material by utilizing magnesiothermic reduction

    CN105762338A

  • Method for preparing silicon / carbon composite material with magnesiothermic reduction process

    CN106374088A

  • Preparation method of lithium ion battery silicon-carbon composite negative electrode material based on magnesiothermic reduction

    CN111834610A

  • Hydrogel-derived silicon-titanium alloy interconnected network material and preparation method and application thereof

    CN109888265A

  • Method for preparing titanium-silicon alloy negative electrode material from silicon waste and titanium-containing slag

    CN113013397A